Expression Profiling of MicroRNAs in Hippocampus of Rats Following Traumatic Brain Injury - 孙婷怡 陈晓瑞 刘子龙 赵丽丽 江永祥 屈国强 王荣帅 黄锶哲 刘良 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
The changes of microRNA expression in rat hippocampus after traumatic brain injury（TBI） were explored. Adult SD rats received a single controlled cortical impact injury, and the ipsilateral hippocampus was harvested for the subsequent microarray assay at three time points after TBI： 1st day, 3rd day and 5th day, respectively. We characterized the microRNA expression profile in rat hippocampus using the microRNA microarray analysis, and further verified microarray results of miR-142-3p and miR-221 using quantitative real-time PCR. Totally 205 microRNAs were identified and up-/down-regu-lated more than 1.5 times. There were significant changes in 17 microRNAs at all three time points post-TBI. The quantitative real-time PCR results of miR-142-3p and miR-221 indicated good consistency with the results of the microarray method. MicroRNAs altered at different time points post-TBI. MiR-142-3p and miR-221 may be used as potentially biological markers for TBI assessment in forensic practice.